Tingkat Pengetahuan Self-Esteem Remaja Pasca Menonton Film Imperfect: Karir, Cinta & Timbangan - Gabriela Cherise; Narwastu Adika Bestari (Calathu: Jurnal Ilmu Komunikasi, 2022)
This research departs from a social phenomenon where a person's sense of self-love and self-acceptance affects the individual's self-esteem. With the development of communication media in this digital era, media products play a big role in influencing the individual's personality through the messages. Therefore, the researcher wants to find out how the message in the film Imperfect: Karir, Cinta & Timbangan influences the audience's level of self-esteem knowledge. So that, researchers will be able to find out how effective the message about self-esteem is delivered through the film Imperfect: Karir, Cinta & Timbangan. The level of knowledge is measured through a questionnaire to determine the extent to which the film is able to affect the audience cognitively with a Likert scale instrument for measurement. The subjects of this preliminary research were 30 teenagers with an age range of 15-20 years, both male and female, who had watched the film Imperfect: Karir, Cinta & Timbangan. The results of this research indicate that most teenagers who have watched the film Imperfect: Karir, Cinta & Timbangan are on average 20 years old and find that their level of knowledge on self-esteem increases which then affects their ability to respect and appreciate themselves. So, after that they can be assertive, able to establish healthy relationships, feel proud of themselves and are able to accept all their shortcomings and strengths. Thus, the role of the film in conveying the message is considered effective enough to give a cognitive influence on the audience. Keywords: knowledge level, film, influence, self-esteem, effectivity